Peranan Terminal Bubulak dan Terminal Laladon Sebagai Terminal di Perbatasan Kota dan Kabupaten Bogor - Siswanto, Adrianus Dwi; Falatehan, A Faroby; Oktaria, Andi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Regional autononn; has created considerable authority fur each autonomous region. MunicipalihJ ofBogar and Bogar district government take advantage of regional autonomy to provide the bestservice to its communities. The Jdnds of these services is to develop Terminal Bubulak Ialadon. Bothterminals have a close distance so many problems arise. This study uses three analysis (analysis oflocations, the analysis of perception and analysis of the role linkages. In addition this study alsoidentifiJ (identify the role of the terminal). This research examined the application of KeputusanMenteri Perhubungan No. 31 Tahun 1995 Tentang Terminal Transportasi Jalan.The results showed the existence of violations of the Minister of Transportation regulations. Bubulakterminal development in accordance with the regulations. However, the construction of the terminalI.aladon break the rules. People still feel the non optimal function of these two terminals. On the otherhand the presence of adjacent terminal 2 is problematical. Serious problem is crowded that createdand low service. For that poliaj recommendation is to combine the two terminals into one node asmandated m; the Decree of the Minister of Transportation.Keywords: Terminal, location, function terminal.